Earnings and firm value: the moderating impact of large deferred taxes and large accruals in Indonesia - Sutopo, Bambang; Adiati, Arum Kusumaningdyah; Siddi, Purnama (Business: Theory and Practice, 2021)
Deferred tax and accruals have the characteristic of causing reported earnings to be above or below normal. Both are permitted to be used by companies in financial reporting. This study examines whether large deferred taxes and large accruals have an impact on the relationship between earnings and firm value. Using a sample that includes 1938 company-year observations for the 2007−2017 periods listed on the Indonesia Stock Exchange (IDX), this study found that large positive deferred taxes with large positive accruals had weakened the relationship between earnings and firm value. In contrast to these results, a large negative deferred tax with a large negative accrual does not have an impact on the relationship between earnings and the firm value. This finding suggests that “liberal” accounting policies that cause reported “above normal” earnings have a negative effect on the association between earnings and firm value. However, “below normal” earnings resulting from “conservative” accounting policies do not affect the association between earnings and firm value. The uniqueness of this study is the incorporation of deferred taxes with accruals with variations in the form of positive versus negative and large versus small. The findings imply that the presentation of financial information with small deferred taxes and small accruals is more beneficial for investors compared to financial information with large positive deferred taxes and large positive accruals. However, results of this study indicate that large negative deferred taxes and large negative accruals, indicating conservative accounting, are not responded differently by investors.